The viscoelastic properties of cork - Mano, J. F. (Journal of materials science, 2002)
The viscoelastic properties of cork (from Quercus suber) have been investigated in the temperature range −40 to 120 ◦ C using the technique of Dynamic Mechanical Analysis (DMA). The results were compared with dielectric data previously reported. A relaxation was detected with a maximum in tan δ at ca 20 ◦ C (f = 1 Hz) and with a mean activation energy of 140 kJ ·mol−1 . A decrease in the intensity of the relaxation and an increase of the storage modulus is observed when cork is previously subjected to an annealing process above 60 ◦ C. This result is in agreement with previously reported dielectric data. Thermogravimetric experiments seem to conﬁrm that such effect could be caused by the desorption of water molecules. Specimens oriented along the prismatic direction presented higher storage modulus than the ones oriented along the transverse prismatic direction. The rheological properties of cork also showed a dependence upon the mechanical mode used during measurements: for example, the stiffness is the highest for the tensile mode and the lowest for the compression mode.
Keywords: Cork; Dynamic mechanical analysis (DMA); Relaxation; viscoelastic properties (voyant)

The viscoelastic properties of cork - Mano, J F (Journal of materials science, 2002)
The viscoelastic properties of cork (from Quercus suber) have been investigated in the temperature range −40 to 120 ◦ C using the technique of Dynamic Mechanical Analysis (DMA). The results were compared with dielectric data previously reported. A relaxation was detected with a maximum in tan δ at ca 20 ◦ C (f = 1 Hz) and with a mean activation energy of 140 kJ ·mol−1 . A decrease in the intensity of the relaxation and an increase of the storage modulus is observed when cork is previously subjected to an annealing process above 60 ◦ C. This result is in agreement with previously reported dielectric data. Thermogravimetric experiments seem to conﬁrm that such effect could be caused by the desorption of water molecules. Specimens oriented along the prismatic direction presented higher storage modulus than the ones oriented along the transverse prismatic direction. The rheological properties of cork also showed a dependence upon the mechanical mode used during measurements: for example, the stiffness is the highest for the tensile mode and the lowest for the compression mode.
Keywords: Cork; Dynamic mechanical analysis (DMA); Relaxation; viscoelastic properties (voyant)